Calcaneal apophysitis: a quantitative radiographic evaluation of the secondary ossification center - Volpon, J. B.; Carvalho, G. D. (Springer, 2002)
Background: Calcaneal apophysitis in children is a self-limited condition that may interfere with walking and physical performance in sports, thus causing concern to the patient and parents. There is still controversy about the significance of the radiographic changes in children with heel pain, since the report of Sever in 1912. One of the reasons is that normal children may display a considerable variation in the radiographic aspects of the secondary ossification center of the calcaneus at different ages. Methods: In this investigation, the developmental aspects of primary and secondary ossification centers of the calcaneus were studied in radiographs obtained from healthy boys and from boys with calcaneal apophysitis. The normal population comprised 392 children and adolescents ranging in age from 6 to 15 years. There were 69 individuals with calcaneal apophysitis ranging in age from 8 to 14 years. Lateral standard radiographs were obtained of both heels, and a copper step wedge was used as a calibration to determine bone density. The following parameters were analyzed on the plain films: time of appearance, fusion and number of fragments of the secondary nucleus, area and bone densitometry of the primary and secondary ossification centers of the calcaneus. Results: In the normal population, the ossification of the secondary nucleus began at 7 years of age, and at 15 years of age, the nucleus was fused in all individuals. In the apophysitis group, the secondary ossification center was present and not fused in all individuals. Both secondary nuclei increased in size with age with no difference between the two groups. Regarding bone density, both the primary and secondary nuclei were less dense in the apophysitis group than their counterparts in the normal population. The most significant difference between the two populations referred to the degree of fragmentation, which was greater in the apophysitis group. Conclusion: Our data showed that the sclerotic aspect of the secondary nucleus of the calcaneus is a normal feature and, therefore, should not be used to establish the diagnosis of Sever's disease. The most consistent difference between the normal and apophysitis group was related to the more fragmented aspect of the secondary nucleus in the latter individuals, which may suggest a mechanical etiology for that condition.
Keywords: calcaneus; apophysitis; ossification center; bone densitometry